2015
DOI: 10.1037/a0039024
|View full text |Cite
|
Sign up to set email alerts
|

Men, depression, and coping: Are we on the right path?

Abstract: Knowledge about proactive strategies that men use to cope with depression and suicide is limited. This narrative review aims to provide an overview and critical appraisal of qualitative studies investigating men’s accounts of strategies used to cope with depression and/or suicidal behavior. A search was conducted of relevant databases to identify qualitative (both pure and mixed method) investigations of men’s experiences of depression and suicidal behavior, as well as the strategies used by men to cope with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 47 publications
4
45
0
5
Order By: Relevance
“…Depressed men's higher likelihood of reporting alcohol and substance misuse may be related to men's general higher incidence rates of alcohol and substance misuse in comparison to women (Brady and Randall, 1999;Kessler et al, 1994). Alternatively, it is possible that alcohol and substance misuse is more intimately linked to depression in men, as a way of self-medication or coping, than in women (Whittle et al, 2015). Differential societal pressures and expectations for men and women are also likely to play a role in the perception and expression of symptoms (Danielsson & Johansson, 2005;Emslie et al, 2006;Ridge, Emslie, & White, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Depressed men's higher likelihood of reporting alcohol and substance misuse may be related to men's general higher incidence rates of alcohol and substance misuse in comparison to women (Brady and Randall, 1999;Kessler et al, 1994). Alternatively, it is possible that alcohol and substance misuse is more intimately linked to depression in men, as a way of self-medication or coping, than in women (Whittle et al, 2015). Differential societal pressures and expectations for men and women are also likely to play a role in the perception and expression of symptoms (Danielsson & Johansson, 2005;Emslie et al, 2006;Ridge, Emslie, & White, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Both this review and other research indicates that men continue to hide their depression in public suggesting there may be a difference between the legitimacy they allow their distress in private and what they consider to be socially acceptable (Spendelow, 2015;Whittle et al, 2015). This suggests that dominant masculinity remains an important point of reference for the way in which men negotiate their experience of depression-even when they cannot, or do not wish to, aspire to this idealized representation of who they should be as men (Galasinski, 2008).…”
Section: Gender and Mental Health Problemsmentioning
confidence: 99%
“…Recent systematic reviews (eg, Seidler, Dawes, Rice, Oliffe, & Dhillon, ; Whittle et al, ) and epidemiological and meta‐analytic studies provide support for consideration of externalizing symptoms as part of the diagnostic profile of depression in men (Cavanagh, Wilson, Kavanagh, & Caputi, ; Martin, Neighbors, & Griffith, ). Further, longitudinal cohort research has suggested that a more inclusive conceptualisation and assessment approach may enable better identification of mental illness in at‐risk individuals (Caspi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%